Determinant of Parents Role in Adolescent Premarital Sex Behavior: An Applicative Model - Nur Alam Fajar; Fenny Etrawati; Widya Lionita (Faculty of Public Health, Hasanuddin University, Makassar, 2019)
Premarital sex behavior had become a serious issue. Preliminary studies show 12 of 30 teenagers who religious, well-educated, and has good family background, were already experienced sexual intercourse. The objective of this study is explaining parents’ role through their knowledge, attitude, perception, facilities given to children, and behavior. This research was conducted at 2017, and using a cross-sectional design. Quantitative data were obtained by 526 population study and interviewing 150 students’ parent from six high schools in Palembang which are selected using multistage random sampling. Multivariate data analysis is processed by Structural Equation Modelling (SEM) Test in statistical application program named Partial Least Square (PLS). This research found that fifty percent of respondent have good knowledge and supportive attitude towards preventive action of premarital sex behavior. There are 62.7% having good perception about the importance of parents’ role. However, 41.3% just perform negatively on preventive sexual behavior in early ages. They usually provide some facilities such as money, motorbike or car, handphone, laptop, and internet at home that can be used to access pornography content. Model analysis proved that knowledge, attitude, perception, and facilities influence 29 percent of adolescent premarital sex behavior caused by improper parenting role